ACL transection results in a posterior shift and increased velocity of contact on the medial tibial plateau. (November 2022) - Chastain, Kalle; Wach, Amanda; Pekmezian, Ashley; Wimmer, Markus A.; Warren, Russell F.; Torzilli, Peter A.; Chen, Tony; Maher, Suzanne A.
Abstract: Our objective was to quantify the effect of ACL transection on dynamic knee joint contact force distributions during simulated gait. Given the prevalence of medial compartment osteoarthritis in un-reconstructed ACL ruptured knees, we hypothesized that changes in contact mechanics after ACL transection would be most prevalent in the medial compartment. Twelve human cadaveric knees were tested using a dynamic knee gait simulator which was programmed to mimic a clinical Lachman exam and gait. An electronic pressure sensor was placed on the medial and lateral tibial plateaus under the menisci to quantify dynamic contact forces before and after ACL transection. Tibial translations and rotations, medial and lateral plateau peak contact stress, and position and velocity of the Weighted Center of Contact (WCoC) were computed. After ACL transection, the tibia translated more anteriorly in the Lachman examination and at heel strike during gait. Changes in contact mechanics across the medial tibial plateau during simulated gait were: an increase in the velocity of WCoC and a posterior shift in the WCoC, both of which occurred at heel strike; increased peak contact forces in the posterior-peripheral quadrant of the tibial plateau at 45% of the gait cycle; and an additional posterior shift in WCoC from 25 to 55% of the gait cycle. The only change in contact mechanics in the lateral plateau was a decrease in WCoC velocity in late stance. This data is suggested to further the study of biomechanical pathways (biomechanical biomarkers) in the relationship between altered knee contact mechanics and chondrocyte metabolic responses after ACL transection.